2016
DOI: 10.1016/j.jdiacomp.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of acute hypoglycemia and hyperglycemia on pro-atherothrombotic biomarkers and endothelial function in non-diabetic humans

Abstract: Background The comparative effects of acute moderate hyperglycemia and hypoglycemia on in-vivo endothelial function together with pro-inflammatory and pro-atherothrombotic responses in healthy individuals have not been determined. Methods To investigate this question 45 healthy subjects were compared during glucose clamp studies consisting of euinsulinemic hyperglycemia and hyperinsulinemic hyperglycemia (plasma glucose 11.1 mmol/L, both with pancreatic clamps) and hyperinsulinemic euglycemia and hyperinsuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
4
21
4
1
Order By: Relevance
“…An increased magnitude of glycemic variability would generate more reactive oxygen species (including nitrotyrosine) in complications-prone cells compared to stable hyperglycemia and preliminary data suggest that protective adaptations induced by constant exposure to hyperglycemia are inadequately activated with intermittent exposure, allowing for more pronounced toxicity (92). Besides, in accordance with other reports (96,97), Pena et al (48) showed that an index of hypoglycaemic risk (i.e., Glycemic Risk Assessment Diabetes Equation-Hypoglycemia), measured over the 48 preceding hours, was a negative predictor of FMD but not of NMD. Noteworthy, hypoglycemia may induce vascular damages in the short and long terms: the hypoglycaemia-induced acute hemodynamic changes may precipitate and aggravate a vascular event during an acute episode (99), while repetition of hypoglycemic events could trigger abnormalities of coagulation, fibrinolysis, and inflammation.…”
Section: Heterogeneitysupporting
confidence: 86%
See 1 more Smart Citation
“…An increased magnitude of glycemic variability would generate more reactive oxygen species (including nitrotyrosine) in complications-prone cells compared to stable hyperglycemia and preliminary data suggest that protective adaptations induced by constant exposure to hyperglycemia are inadequately activated with intermittent exposure, allowing for more pronounced toxicity (92). Besides, in accordance with other reports (96,97), Pena et al (48) showed that an index of hypoglycaemic risk (i.e., Glycemic Risk Assessment Diabetes Equation-Hypoglycemia), measured over the 48 preceding hours, was a negative predictor of FMD but not of NMD. Noteworthy, hypoglycemia may induce vascular damages in the short and long terms: the hypoglycaemia-induced acute hemodynamic changes may precipitate and aggravate a vascular event during an acute episode (99), while repetition of hypoglycemic events could trigger abnormalities of coagulation, fibrinolysis, and inflammation.…”
Section: Heterogeneitysupporting
confidence: 86%
“…These 2 studies, in children with type 1 diabetes, failed to detect significant correlation between FMD and glycemic variability, as assessed using 2-week, seven-point, self-monitored blood glucose logs (14) or 48-h continuous glucose monitoring (48). However, as previous in vitro (92) and in vivo (21,(93)(94)(95)(96)(97)(98), studies suggested a possible deleterious impact of glycemic variability on vascular function, further studies are needed to better explore the strength, conditions and mechanisms of this impact. An increased magnitude of glycemic variability would generate more reactive oxygen species (including nitrotyrosine) in complications-prone cells compared to stable hyperglycemia and preliminary data suggest that protective adaptations induced by constant exposure to hyperglycemia are inadequately activated with intermittent exposure, allowing for more pronounced toxicity (92).…”
Section: Heterogeneitymentioning
confidence: 92%
“…Another study observed increased CD40 expression and platelet–monocyte aggregation during acute hypoglycemia in both nondiabetic and T1D subjects . A recent study on 45 healthy subjects compared inflammatory and proatherosclerotic biomarkers released during euinsulinemic hyperglycemia observed an increase in plasminogen activator inhibitor‐1 (PAI‐1) and TNF‐α levels during hypoglycemia . PAI‐1 is a protein that inhibits activators of plasminogen and fibrinolysis like tissue plasminogen activator, while TNF‐α has been shown to facilitate activation of the coagulation cascade .…”
Section: The Effect Of Hypoglycemia On Procoagulant Mechanismsmentioning
confidence: 99%
“…55 A recent study on 45 healthy subjects compared inflammatory and proatherosclerotic biomarkers released during euinsulinemic hyperglycemia observed an increase in plasminogen activator inhibitor-1 (PAI-1) and TNF-␣ levels during hypoglycemia. 56 PAI-1 is a protein that inhibits activators of plasminogen and fibrinolysis like tissue plasminogen activator, while TNF-␣ has been shown to facilitate activation of the coagulation cascade. 57 These studies demonstrate activation of hemostatic mechanisms by exposure to hypoglycemia.…”
Section: The Relation Of Hypoglycemia With Thrombotic and Hemostaticmentioning
confidence: 99%
“…Norepinephrine causes vasoconstriction in most arteries and also transiently increases heart rate, resulting in increased sympathetic tone [40]. The primary source of circulating norepinephrine is spillover from sympathetic nerves innervating blood vessels, and recent work has shown that hyperglycemic-hyperinsulinemia signi cantly increases circulating norepinephrine (but not epinephrine) in healthy humans [41]. In contrast, insulin has vasodilatory effects, with insulinmediated vasodilation and glucose uptake being functionally linked in humans [42].…”
Section: Discussionmentioning
confidence: 99%